Who engaged more online sexual activities, younger or older adult? Implication for marital, couple and family counseling - Hassan, Siti Aishah; Mohd Ayub, Ahmad Fauzi; Hawafi, Harisa; Ghoroghi, Soudabeh (Human Resource Management Academic Research Society, 2017)
The objective of this study is to describe the level of cybersex engagement among adult and to compare mean difference between younger and older adults. An online survey via google.doc has been used to collect data among Facebook user who engaged in cybersex. To date, a total of 202 respondents voluntarily participated in this study. Snowball sampling technique was employed among Facebook users initiated from a public university in Malaysia. Instrumentations used were the adapted Internet SST, and adapted ASAII Data was analyzed using descriptive analysis and t-test. The results show that the level of sexual engagement is at low level and older adult engaged more in comparison to younger adult. The findings of this study are unlikely to be useful for generalization due to the non-probability sample, yet they remain suggestive. Theoretical and practical implication for marital, couple and family counselling research are recommended. Finally, implication for future research is suggested.